Good Corporate Governance Memoderasi Pengaruh Earnings Management dan Likuiditas pada Kualitas Laba - Putra, I Ketut Mandi Wira; Widanaputra, Anak Agung Gde Putu (E-Jurnal Akuntansi; Vol 31 No 8 (2021)DO - 10.24843/EJA.2021.v31.i08.p13, 2021)
The purpose of this study is to obtain empirical evidence on the effect of earnings management and liquidity on earnings quality, with good corporate governance serving as a moderating variable, in companies ranked by the Corporate Governance Perception Index (CGPI). This study employs the associative method, with data gathered from non-participant observations. Purposive sampling was used to determine the sample, and 35 firm-year were obtained during the study period. The Moderated Regression Analysis (MRA) technique was used for data analysis. According to the findings, good corporate governance modifies the relationship between earnings management and earnings quality. Furthermore, according to the findings of this study, good corporate governance has no effect on the relationship between liquidity and earnings quality. Keywords: Earnings Management ; Liquidity; Earnings Quality; Good Corporate Governance.